Ultrafine CoO nanoparticles and Co-N-C lamellae supported on mesoporous carbon for efficient electrocatalysis of oxygen reduction in zinc-air batteries. (20th October 2021) - Wan, Xiaohan; Guo, Xingmei; Duan, Mengting; Shi, Jing; Liu, Shanjing; Zhang, Junhao; Liu, Yuanjun; Zheng, Xiangjun; Kong, Qinghong
Highlights: A coadsorption-pyrolysis method was used to prepare CoO/Co-N-C on mesoporous carbon. Ultrafine CoO and Co-N-C lamellae were the electrocatalytically active species. Mesoporous carbon as the substrate enabled efficient mass and charge transport. Co/Co-N-C/MC had excellent activity and stability for the oxygen reduction reaction. A zinc-air battery with high peak power density and specific capacity was fabricated. Abstract: Designing and synthesizing high-efficiency non-precious metal electrocatalysts are of great significance for electrochemical reduction of oxygen. A simple coadsorption-pyrolysis method is developed to synthesize ultra-small CoO nanoparticles and Co-N-C lamellae supported on ordered mesoporous carbon (MC). The optimized CoO/Co-N-C/MC electrocatalyst has good catalytic activity for oxygen reduction reaction (ORR) with a half-wave potential of 0.78 V vs. RHE and a limiting current density of 5.01 mA cm −2 . The high ORR activity, together with the superior stability compared with Pt/C, make it a good choice as cathode catalyst in zinc-air batteries (ZABs). The as-assembled ZAB has a high open circuit voltage of 1.397 V and a specific capacity of 842 mAh gZn −1 at 10 mA cm −2 . The good performance is attributed to the abundant ultrafine CoO particles and Co-N-C lamellae as catalytic active sites, as well as the mesoporous substrate for efficient mass/charge transport. Graphical abstract: Image, graphical abstract